Regio- and Chemoselective Synthesis of 4,6-Dithia-1,2,9-triazaspiro[4.4]non-2-en-8-ones through an Ultrasound-Promoted One-Pot Sequential Pseudo-Five-Component Reaction - Alizadeh, Abdolali; Chelebari, Ebrahim Amir; Rezaiyehraad, Reza (Synthesis, 2024)
Spiro-heterocycles have attracted significant interest due to their unique biological properties with fewer side effects compared to traditional drugs. Herein, a novel method is reported for the synthesis of a series of spiro-heterocycles possessing a quinoline motif. The strategy utilizes rhodanine derivatives, hydrazonoyl chlorides, and 2-chloroquinoline-3-carbaldehyde, and proceeds via a one-pot sequential pseudo-five-component reaction. The reactions are found to proceed in a regioselective and chemoselective manner.
Keywords: rhodanine; hydrazonoyl chlorides; 2-chloroquinoline-3-carbaldehyde; 4,6-dithia-1,2,9-triazaspiro[4.4]non-2-en-8-ones; five-component reaction; regioselective; chemoselective; ultrasound